TIPOLOGI MINAT ANAK MUDA TERHADAP LEMBAGA KEUANGAN MIKRO SYARIAH BERDASARKAN LAYANAN MOBILE BANKING - Hasbi Assidiki Mauluddi (INTERNAL (Information System Journal), 2019)
This research was conducted to find out typical interest among young people towards Islamic microfinance institutions (LKMS) based on mobile banking services. The research data was taken by purposive sampling method on high school students in Kabupaten Bandung as many as 120 people. The data obtained is then processed using K-means cluster analysis. The results of the study show that the majority of young people in rural areas are interested in becoming customers of Islamic microfinance institutions (LKMS). This is due to the strong attractiveness of LKMS products, satisfaction using LKMS mobile banking applications, knowledge of LKMS institutions, and knowledge of LKMS products. The majority of these youth are members of cluster 2. While cluster members 1 and cluster 3 are minority clusters. In the minority clusters, weak knowledge of LKMS institutions and products causes a weak interest in young people in the use of LKMS mobile banking applications. This is not the case in cluster 2. Thus, the strong interest of young people in the application of Mobile banking LKMS membership is closely related to their knowledge of LKMS institutions and products.